2020
DOI: 10.21203/rs.2.21773/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Taxonomic scheme of the order Chaetophorales (Chlorophyceae, Chlorophyta) based on Chloroplast genomes

Abstract: Background: Order Chaetophorales currently includes six families, namely Schizomeridaceae, Aphanochaetaceae, Barrancaceae, Uronemataceae, Fritschiellaceae, and Chaetophoraceae. The phylogenetic relationships of Chaetophorales have been inferred primarily based on short and less informative rDNA sequences. This study aimed to phylogenetically reconstruct order Chaetophorales and determine the taxonomic scheme and to further the current understanding of the evolution of order Chaetophorales.Results: In the prese… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Phylogenetic analyses based on concatenated seven genes presented limited ability to resolve the phylogenetic relationships within Chlorophyceae, especially those of the OCC clade. However, within the order Chaetophorales, the relationships were highly consistent with those based on the concatenated 58 protein-coding genes (Liu et al, 2020). The results obtained suggested that these concatenated seven genes are reliable and could replace phylogenetic analyses based on chloroplast genomes to some extent in determining the internal branching relationship of Chaetophorales.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Phylogenetic analyses based on concatenated seven genes presented limited ability to resolve the phylogenetic relationships within Chlorophyceae, especially those of the OCC clade. However, within the order Chaetophorales, the relationships were highly consistent with those based on the concatenated 58 protein-coding genes (Liu et al, 2020). The results obtained suggested that these concatenated seven genes are reliable and could replace phylogenetic analyses based on chloroplast genomes to some extent in determining the internal branching relationship of Chaetophorales.…”
Section: Discussionsupporting
confidence: 66%
“…Different genes support diverse topologies. Topology I is more reliable and has been verified using chloroplast genomes (Liu et al, 2020), whereas Topology II has been verified by nuclear genes (Caisová et al, 2011(Caisová et al, , 2013Liu et al, 2019Liu et al, , 2020. In the present study, 19 genes supported Topology I, and only 4 genes supported Topology II, which might explain why the phylogenetic trees constructed with concatenated 58 protein-coding genes supported Topology I for its absolute advantage in terms of the number of supported genes and variable information sites (Liu et al, 2020).…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations